Hak Asasi Manusia dan Perbatasan: Mengembalikan Kerugian Hak-Hak Masyarakat Adat Sama Dilaut di Filipina Selatan - Kriselle Marie Calica Aquino (Jurnal HAM, 2024)
The Sama Dilaut, identifying themselves as a seafaring people, consider the sea central to their homeland and cultural identity. Despite formal recognition of their procedural rights under international and domestic legal frameworks, they persist on the periphery of societal hierarchies, not due to material scarcity but because of profound deficits in capabilities and freedoms. This study shifts focus from material deprivation to rights deprivation, specifically examining how their indigenous perspectives are marginalized in the interpretation and realization of human rights. Utilizing qualitative methods, particularly phenomenology and key informant interviews, this research investigates the multifaceted experiences of deprivation faced by the Sama Dilaut across different contexts: on land, at sea, and within both community (horizontal) and state (vertical) frameworks. Furthermore, it critically analyzes potential pathways and strategies to enable them to fully exercise their rights and freedoms. Central to the findings is the Sama Dilaut's conceptualization of human rights ('kapatut manusiya'), which underscores four primary areas of deprivation compared to desired freedoms: knowledge and education ('pangalaman' or 'panghati'), indigenous culture, spirituality, and religious beliefs ('pangaddatan' and 'pag-omboh' or 'pag-paybahau'), traditional and diversified economic livelihoods ('pag-usaha' or 'pagkalluman'), and socio-political leadership and participation ('panglima' or 'nakura'). This study contributes significantly to reframing the discourse on international human rights by foregrounding the experiences of the Sama Dilaut, a community characterized by their deprivation of freedoms despite their rich maritime heritage and worldview. By amplifying their voices and highlighting their lived realities, this research advocates for a more inclusive approach to human rights that incorporates and respects diverse indigenous perspectives. Ultimately, it seeks to inform policy and advocacy efforts aimed at addressing systemic inequalities and promoting the full realization of rights for marginalized communities such as the Sama Dilaut.